Performance evaluation of fisheries extension officers (Case study of civil servant fishery extension workers in Kutai Kartanegara District) - Putra, Fandi Eka; Saleha , Qoriah; Sugiharto, Eko (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
The purpose of this study was to assess the implementation of the performance of fishery instructors in Kutai Kartanegara Regency based on 14 extension indicators in carrying out the duties and functions of fishery instructors (Decree Number: 192/KEP-BRSDM/2020). This type of research is a type of descriptive statistical research. The research method used is the census method. The population in this study were 4 Civil Servant Fisheries Extension Workers in Kutai Kartanegara Regency. The selection of the sample was by census, meaning that the four fisheries extension officers were sampled. The results of the evaluation of the performance of civil servant fisheries extension officers in Kutai Kartanegara Regency based on Decree Number: 192/KEP-BRSDM/2020 cumulatively are in the high category with a score of 80.5 which is between 70.02-90.00. This value can be interpreted that the performance of civil servant extension officers in Kutai Kartanegara Regency has been carried out well, although not optimal.